'Let our emotions tell the story': An exploration of emotion management in Chinese proactive workgroup socialization. (July 2019) - Guo, Yijia
This exploratory qualitative study augments extant literature in organizational studies on workplace emotion by examining emotion management in the Chinese proactive workgroup socialization process. The study sought to gain insight into Chinese newcomers' emotional experiences, the ways in which Chinese newcomers negotiated their understanding of emotion in the workplace, and the implications of emotional maturity from the perspective of Chinese employees. More importantly, this study exposed differences in proactive socialization between a Chinese bureaucratic office and western organizations. Individual and focus group interviews were conducted with 22 veterans and new employees in a Chinese governmental agency. A modified constant comparative analysis revealed three primary aspects that delineate the Chinese workplace as it relates to emotion management during socialization: (i) there are three salient types of emotion that occurred in Chinese workgroups; (ii) Chinese work settings are characterized by perceptions of emotional maturity, with a cultural emphasis on a holistic mindset, an indicator of personal growth and a shared goal; and (iii) more importantly, Chinese newcomers play an active role in negotiating and modifying established cultures.